Peningkatan Motorik Kasar Melalui Pembelajaran Daring Berbasis Whats App - Andini, Diah Puspita; Marlinah, Marlinah; Nurchahyani, Nurchahyani; Apriyanti, Sesiyana; Silaban, Esnirani; Yuliantina, Irma (Efektor, 2021)
Improving learning through rough motoric activities using WhatsApp application at RA Al Muttaqin. This research was implemented using offline (Visit School) and online (WhatsApp applications) methods as a problem solver for teaching and learning activities (KBM) at RA Al Muttaqin during the Covid-19 pandemic. Based on the results of motoric physical activity through WhatsApp learning was applied by making video of learning to know children’s rough motoric development. Generally, WhatsApp-based online learning challenges teacher’s creativity, in planning fun and interesting learning programs by developing collaboration between teachers, parents and participants, that is become the best solution in the Covid-19 pandemic that demands to take care of the physical.